Investigation on thermodynamics of ion-slicing of GaN and heterogeneously integrating high-quality GaN films on CMOS compatible Si(100) substrates. Issue 1 (December 2017) - Huang, Kai; Jia, Qi; You, Tiangui; Zhang, Runchun; Lin, Jiajie; Zhang, Shibin; Zhou, Min; Zhang, Bo; Yu, Wenjie; Ou, Xin; Wang, Xi
Abstract Die-to-wafer heterogeneous integration of single-crystalline GaN film with CMOS compatible Si(100) substrate using the ion-cutting technique has been demonstrated. The thermodynamics of GaN surface blistering isin-situ investigated via a thermal-stage optical microscopy, which indicates that the large activation energy (2.5 eV) and low H ions utilization ratio ( 6%) might result in the extremely high H fluence required for the ion-slicing of GaN. The crystalline quality, surface topography and the microstructure of the GaN films are characterized in detail. The full width at half maximum (FWHM) for GaN (002) X-ray rocking curves is as low as 163 arcsec, corresponding to a density of threading dislocation of 5 × 107 cm−2 . Different evolution of the implantation-induced damage was observed and a relationship between the damage evolution and implantation-induced damage is demonstrated. This work would be beneficial to understand the mechanism of ion-slicing of GaN and to provide a platform for the hybrid integration of GaN devices with standard Si CMOS process.